Social and Emotional Competences in Spain: A Comparative Evaluation Between Spanish Needs and an International Framework Based on the Experiences of Researchers, Teachers, and Policymakers - Aguilar, Pilar; Lopez-Cobo, Isabel; Cuadrado, Francisco; Benítez, Isabel (Frontiers in Psychology, 2019)
Critical aspects in the field of education are currently related to low levels of socioemotional competences and high rates of school dropouts. However, there are no standard practices or guidelines for helping countries to assess and train social and emotional competences. To overcome this limitation, the project Learning to be (L2B) aims to propose a comprehensive model of the assessment and development of social and emotional competences that bring together policymakers, researchers, teachers, school authorities and learners from different participating countries: Finland, Italy, Latvia, Lithuania, Portugal, Slovenia, and Spain. The project attempts to create an international framework for regulating activities and supporting teachers working on the social and emotional competences of the students and to provide tools which can be used across countries. The aim of the paper is to describe how L2B has been developed in Spain by analyzing the contributions of the international framework and extracting the specific needs in the Spanish context. Specifically, we describe two products of the project: a) the process for creating a toolkit, a tool focused on creating activities and materials for helping teachers develop social and emotional competences of students and b) the results of an exploratory study in Spain in which social and emotional competences are assessed and compared to the international framework. First, we explain the definition of social and emotional competences used for creating the toolkit. Second, we analyze responses of Spanish students to questionnaires administered before applying the toolkit in the schools. The paper describes social and emotional competences in Spain and evaluates the overlap between relevant variables in Spain and those used for developing the toolkit, the international tool. Specific needs in Spain are discussed, as well as the contribution of the project for promoting the improved development of students’ social and emotional competences, improving learning outcomes and stronger social cohesion in schools and local communities, as well as the utility of the results for creating new educational policies.